2005
DOI: 10.1110/ps.041216105
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and crystallographic studies on 2‐(β‐D‐glucopyranosyl)‐5‐methyl‐1, 3, 4‐oxadiazole, ‐benzothiazole, and ‐benzimidazole, inhibitors of muscle glycogen phosphorylase b. Evidence for a new binding site

Abstract: In an attempt to identify leads that would enable the design of inhibitors with enhanced affinity for glycogen phosphorylase (GP), that might control hyperglycaemia in type 2 diabetes, three new analogs of ␤-Dglucopyranose, 2-(␤-D-glucopyranosyl)-5-methyl-1, 3, 4-oxadiazole, -benzothiazole, and -benzimidazole were assessed for their potency to inhibit GPb activity. The compounds showed competitive inhibition (with respect to substrate Glc-1-P) with K i values of 145.2 (±11.6), 76 (±4.8), and 8.6 (±0.7) M, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 33 publications
1
58
0
1
Order By: Relevance
“…The significant difference in the binding strength of these compounds was ascribed to the H-bond forming capacity of the NH moiety in 3 to the main chain CO of His377 next to the catalytic site of the protein as revealed by X-ray crystallography of the RMGPb-3 complex. 22 Further studies with each isomer of C-glucosyl oxadiazoles 21,23,24 4−6 indicated that the constitution of the heterocycle significantly influenced the inhibition. The 1,2,4-triazoles 7, with the heteroatoms in the same relative position as in the oxadiazoles, proved even stronger inhibitors.…”
mentioning
confidence: 99%
“…The significant difference in the binding strength of these compounds was ascribed to the H-bond forming capacity of the NH moiety in 3 to the main chain CO of His377 next to the catalytic site of the protein as revealed by X-ray crystallography of the RMGPb-3 complex. 22 Further studies with each isomer of C-glucosyl oxadiazoles 21,23,24 4−6 indicated that the constitution of the heterocycle significantly influenced the inhibition. The 1,2,4-triazoles 7, with the heteroatoms in the same relative position as in the oxadiazoles, proved even stronger inhibitors.…”
mentioning
confidence: 99%
“…For the inhibitory glucose derivatives (Gimisis, 2010;Praly & Vidal, 2010;Somsák, 2011;Somsák et al, 2003;Somsák et al, 2005) protein crystallography showed primary binding to the catalytic site of the enzyme. Some glucose analogues can also occupy the new allosteric site , and the benzimidazole-site was evidenced by a 2-(-Dglucopyranosyl)-benzimidazole (Chrysina et al, 2005). The studied O-, and S-glucopyranosides proved very weak inhibitors with K i values in the 2000-25000 M and 650-21100 M, respectively (Somsák et al, 2003;Somsák et al, 2005).…”
Section: Glucose Analogue Inhibitors Of Glycogen Phosphorylasementioning
confidence: 95%
“…Protein crystallographic studies (Chrysina, 2010;Oikonomakos, 2002) revealed the existence of six binding sites in GP (Fig. 1): the catalytic, the inhibitor, the allosteric, the glycogen storage, and the new allosteric sites, as well as the newly discovered benzimidazole site (Chrysina et al, 2005). Each binding site can be targeted by small molecules, and a large variety of inhibitors were tested as described in recent reviews (Loughlin, 2010;Somsák et al, 2008).…”
Section: Glucose Analogue Inhibitors Of Glycogen Phosphorylasementioning
confidence: 99%
“…The corresponding thioamide remained also intact on treatment with benzhydrazide even at elevated temperature (conditions adapted from reports for non-sugar 29,30 or ribofuranose 19 based compounds) as well as under microwave irradiation. Therefore, application of more reactive precursors such as Operbenzoylated C-(b-D-glucopyranosyl)formimidate, 9 (1), -formamidrazones (3,4), -formamidine (5) and C-(b-D-glucopyranosyl) formyl chloride, 31 (13), was envisaged for the construction of the target triazoles. Synthesis of formamidrazone 3 was carried out by the treatment of ethyl C-(b-D-glucopyranosyl)formimidate 9 (1) with hydrazine hydrate in EtOH (Scheme 1).…”
Section: Synthesesmentioning
confidence: 99%